2015
DOI: 10.1097/rti.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodule Characterization, Including Computer Analysis and Quantitative Features

Abstract: Pulmonary nodules are commonly detected in computed tomography (CT) chest screening of a high-risk population. The specific visual or quantitative features on CT or other modalities can be used to characterize the likelihood that a nodule is benign or malignant. Visual features on CT such as size, attenuation, location, morphology, edge characteristics, and other distinctive "signs" can be highly suggestive of a specific diagnosis and, in general, be used to determine the probability that a specific nodule is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 147 publications
(152 reference statements)
0
35
0
6
Order By: Relevance
“…They concluded that Bannual spiral CT scanning can detect lung cancer that is curable.^Results from more recent large screening trials such as the National Lung Screening Trial have contributed to our current knowledge on the risk of lung cancer and have proven that there can be a benefit to overall survival in some high-risk populations [4]. Furthermore, these trials have clarified our understanding of the importance of nodule size and other morphological characteristics [5]. The implication is clear: a validated test of high sensitivity, high specificity, low cost, and low radiation dose-a test that is currently lacking-would be potentially useful in clinical practice and management of disease.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that Bannual spiral CT scanning can detect lung cancer that is curable.^Results from more recent large screening trials such as the National Lung Screening Trial have contributed to our current knowledge on the risk of lung cancer and have proven that there can be a benefit to overall survival in some high-risk populations [4]. Furthermore, these trials have clarified our understanding of the importance of nodule size and other morphological characteristics [5]. The implication is clear: a validated test of high sensitivity, high specificity, low cost, and low radiation dose-a test that is currently lacking-would be potentially useful in clinical practice and management of disease.…”
Section: Introductionmentioning
confidence: 99%
“…To perform the selection of the nodules according to their diameters, we initially estimated their sizes which were then attached to our database, as the LIDC-IDRC original database did not contain. The size of a nodule was calculated as a simple 2D measure of the greatest diameter, which can be realized in the axial plane along the axis of the longest diameter [Bartholmai et al 2015]. These approximations consisted of calculating the Euclidean distance between the minimum and maximum coordinates in the respective x and y axes of all slices of a nodule.…”
Section: Small Lung Nodule Selectionmentioning
confidence: 99%
“…2000], a nodule can be as a small nodule when it has a diameter of less than 10mm. However, Bartholmai et al [Bartholmai et al 2015] affirm that tests have already shown that nodules with a diameter less than 5mm are probably benign, even in cases of high-risk patients, which makes it uninteresting to work with nodules predisposed to be benign. So, the threshold chosen for this work was nodules greater equal to 5mm and less than 11mm.…”
Section: Small Lung Nodule Selectionmentioning
confidence: 99%
“…Most SPN found in CT scans are benign, even among high-risk populations such as smokers. A few algorithms or prediction models based on nodule features in the CT scan have been developed; however, their accuracy remains unsatisfactory (7). On one hand, timely identification of malignant nodules is crucial because they represent a localized disease and are potentially curable.…”
Section: Introductionmentioning
confidence: 99%